2012
DOI: 10.1088/0022-3727/45/42/425202
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of hard x-rays emitted from metre-scale positive discharges in air

Abstract: We investigate structure and evolution of long positive spark breakdown; and we study at which stage pulses of hard X-rays are emitted. Positive high-voltage pulses of standardized lightning impulse wave form of about 1 MV were applied to about 1 meter of ambient air. The discharge evolution was imaged with a resolution of tens of nanoseconds with an intensified CCD camera. LaBr 3 (Ce + ) scintillation detectors recorded the X-rays emitted during the process. The voltage and the currents on both electrodes wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
138
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(156 citation statements)
references
References 30 publications
14
138
3
1
Order By: Relevance
“…The two types of distributions considered produce similar results for the mean energy and for the total number of photons. Despite being slightly different from previous estimates reported in [7,[13][14][15][16], the values derived in this study are of the same order of magnitude as these previous estimates.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The two types of distributions considered produce similar results for the mean energy and for the total number of photons. Despite being slightly different from previous estimates reported in [7,[13][14][15][16], the values derived in this study are of the same order of magnitude as these previous estimates.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though the negative discharge development was simplified in the model, the main idea that the streamer encounters can cause X-ray emissions has been supported by recent experimental observations. In the case of positive breakdown in the laboratory, X-rays indeed appear when the positive streamers from the high voltage electrode meet the negative streamer that originates from the ground [7]. In recent studies, X-ray emissions were observed during the initiation of negative leaders from the high voltage electrode [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fermi Gamma-Ray Space Telescope detected a clear positron annihilation signal over Egypt from a thunderstorm over Zambia where the two events were connected in space and time through a geomagnetic field line (that electrons and positrons follow sufficiently high in the ionosphere where collisions with air molecules are negligible; Briggs et al 2011). High-energy X-rays were also detected from lightning leaders approaching ground and from long sparks in the laboratory, see, e.g., Kochkin et al (2012). We refer to the review by Dwyer and Uman (2014).…”
Section: Thundercloud Electrification Lightning and Transient Luminomentioning
confidence: 99%
“…The recent discoveries of the Terrestrial Gamma ray Flashes (TGF) by Fishman et al [1994] and the high-energy emissions produced by lightning [Moore et al, 2001] promoted the interest of the atmospheric electricity community in the high energy emissions produced by laboratory discharges at air [e.g. Dwyer et al, 2005;Nguyen et al, 2008;Rahman et al, 2008;Montanyà, 2010 and2011;Kochkin et al,2012]. One of the interests in high voltage experiments is to understand the mechanisms of the production of energetic radiation that occurs in lightning and may probably share similar properties than the intense TGF to space.…”
Section: Introductionmentioning
confidence: 99%